Learning healthcare systems and rapid learning in radiation oncology: Where are we and where are we going?. (November 2021) - Price, Gareth; Mackay, Ranald; Aznar, Marianne; McWilliam, Alan; Johnson-Hart, Corinne; van Herk, Marcel; Faivre-Finn, Corinne
Highlights: Learning healthcare systems and rapid learning are widely discussed in the literature. Interest in these concepts is not matched by reports of their practical use. There is no consensus on rapid-learning experimental and statistical design. Rapid learning must balance evidence quality with ethical acceptability and practicality. Lack of practical demonstration of rapid learning is a barrier to widespread uptake. Abstract: Learning health systems and rapid-learning are well developed at the conceptual level. The promise of rapidly generating and applying evidence where conventional clinical trials would not usually be practical is attractive in principle. The connectivity of modern digital healthcare information systems and the increasing volumes of data accrued through patients' care pathways offer an ideal platform for the concepts. This is particularly true in radiotherapy where modern treatment planning and image guidance offers a precise digital record of the treatment planned and delivered. The vision is of real-world data, accrued by patients during their routine care, being used to drive programmes of continuous clinical improvement as part of standard practice. This vision, however, is not yet a reality in radiotherapy departments. In this article we review the literature to explore why this is not the case, identify barriers to its implementation, and suggest how wider clinical application might be achieved.